PRINCIPAL'S POLICY IN PREVENTING BULLYING AGAINST CHILDREN WITH SPECIAL NEEDS (CSN) IN MIN 9 BANDA ACEH - Putri Kamila; Sri Rahmi (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2026)
Bullying against Children with Special Needs (CSN) is a serious issue in the implementation of inclusive education in madrasahs. The prevention of bullying requires well-planned policies and strategies from the head of the madrasah and the involvement of all school members. This study aims to analyze the policies and strategies of the head of the madrasah in preventing bullying against CSN at MIN 9 Banda Aceh, as well as to identify internal and external constraints in their implementation. This study employed a qualitative approach using a descriptive method. Data were collected through interviews, observations, and documentation involving the head of the madrasah, the vice principal for student affairs, and homeroom teachers as research informants. Data validity was ensured through source triangulation.The results show that bullying prevention policies at MIN 9 Banda Aceh are based on the vision and mission of an inclusive madrasah that emphasize the values of justice, equality, and student protection. Prevention strategies are implemented through the cultivation of empathy values, strengthening the role of teachers, inclusive classroom management, and parental involvement. However, the implementation still faces constraints such as limited resources, limited time for guidance, and the influence of the social environment. This study concludes that effective prevention of bullying against CSN requires systematic policies, inclusive leadership, and sustainable collaboration.